La Responsabilidad Penal de las personas dedicadas a la Medicina Tradicional de los Pueblos y Nacionalidades Indígenas en Ecuador, al generarse la muerte de una persona. - Reyes Zhingre, Yessenia Stefania (2023)
The Curriculum Integration Research is titled: "The criminal responsibility of traditional medicine practitioners of Indigenous peoples and Nationalities in Ecuador, when the death of a person occurs". An analysis was carried out because in Ecuador there is a practice of ancestral traditional medicine of indigenous peoples, which is based on the approach of ancestral knowledge and beliefs for the physical and mental well-being and care of individuals. The State, as the governing entity, recognizes ancestral practices in the supreme norm, and as such, must guarantee and protect against any imminent risk caused by agents who provide welfare services, however, there is no specific legal body, apart from the Organic Health Law, which does not provide a way to prove the existence of the respective regulation by the entity and gives the possibility of abuse of ancestral knowledge. In Ecuador, many health services linked to traditional medicine do not have the necessary effectiveness and efficiency to offer and guarantee the proper use of ancestral knowledge, and that is why any subject or individual can self-consider as an agent or practitioner of traditional medicine. Unfortunately, there is less supervision regarding the safety of the use and practice of traditional medicine on indigenous regions, so those who use it are exposed to potential risks, and the analysis of the following violated rights has been considered: life, health, heritage, and abuse of ancestral traditional knowledge. Because wrong practice can have consequences such as death, it is important to analyze the aspects of criminal responsibility that have been applied or not to people who practice this form of medicine. In this Curriculum Integration Research, materials and methods were used and applied that allowed its development. Surveys and interviews were conducted with legal professionals, health professionals, and ancestral agents, whose results were used to propose the development of propositional guidelines that ensure the protection of individuals who are involved in the use of ancestral medicine and at the same time establish obligations and responsibilities that derive from the practice.